Pengembangan LKPD Koding dan Kecerdasan Artifisial Berbasis Project-Based Learning untuk Meningkatkan Keterampilan Berpikir Komputasional Siswa Kelas V Sekolah Dasar - Baina Qodriani; Otib Satibi Hidayat; Herlina Usman (Jurnal Ragam Pengabdian, 2026)
The implementation of Coding and Artificial Intelligence (KKA) learning in elementary schools still faces several challenges, particularly the limited availability of instructional materials that suit students’ characteristics and support the development of computational thinking skills. This study aimed to develop a Project-Based Learning (PjBL)-based student worksheet (LKPD) that is feasible and effective in improving elementary students’ computational thinking skills. The research employed a Research and Development (R&D) method using the 4D model, consisting of the define, design, develop, and disseminate stages. The participants included one material expert, one media expert, one language expert, and 30 fifth-grade students. Data were collected through observations, interviews, questionnaires, expert validation, and pre-test and post-test assessments. Validation results showed feasibility scores of 92% from the material expert, 90% from the media expert, and 67.24% from the language expert, indicating that the worksheet was feasible to highly feasible. The implementation results revealed an increase in students’ average scores from 55.33 to 85.33. The average N-Gain score was 0.62, indicating moderate improvement. The findings demonstrate that the developed worksheet is suitable for Coding and Artificial Intelligence learning and effectively enhances computational thinking skills. Its novelty lies in integrating Coding and Artificial Intelligence with Project-Based Learning specifically for elementary school students.